European Association of Urology Guidelines on Muscle-invasive and Metastatic Bladder Cancer: Summary of the 2020 Guidelines - Witjes, J. Alfred; Bruins, Harman Max; Cathomas, Richard; Compérat, Eva M.; Cowan, Nigel C.; Gakis, Georgios; Hernández, Virginia; Linares Espinós, Estefania; Lorch, Anja; Neuzillet, Yann; Rouanne, Mathieu; Thalmann, George N.; et al. (European urology, 2021)
This overview presents the updated European Association of Urology (EAU) guidelines for muscle-invasive and metastatic bladder cancer (MMIBC). To provide practical evidence-based recommendations and consensus statements on the clinical management of MMIBC with a focus on diagnosis and treatment. A broad and comprehensive scoping exercise covering all areas of the MMIBC guideline has been performed annually since its 2017 publication (based on the 2016 guideline). Databases covered by the search included Medline, EMBASE, and the Cochrane Libraries, resulting in yearly guideline updates. A level of evidence and a grade of recommendation were assigned. Additionally, the results of a collaborative multistakeholder consensus project on advanced bladder cancer (BC) have been incorporated in the 2020 guidelines, addressing those areas where it is unlikely that prospective comparative studies will be conducted. Variant histologies are increasingly reported in invasive BC and are relevant for treatment and prognosis. Staging is preferably done with (enhanced) computerised tomography scanning. Treatment decisions are still largely based on clinical factors. Radical cystectomy (RC) with lymph node dissection remains the recommended treatment in highest-risk non–muscle-invasive and muscle-invasive nonmetastatic BC, preceded by cisplatin-based neoadjuvant chemotherapy (NAC) for invasive tumours in “fit” patients. Selected men and women benefit from sexuality sparing RC, although this is not recommended as standard therapy. Open and robotic RC show comparable outcomes, provided the procedure is performed in experienced centres. For open RC 10, the minimum selected case load is 10 procedures per year. If bladder preservation is considered, chemoradiation is an alternative in well-selected patients without carcinoma in situ and after maximal resection. Adjuvant chemotherapy should be considered if no NAC was given. Perioperative immunotherapy can be offered in clinical trial setting. For fit metastatic patients, cisplatin-based chemotherapy remains the first choice. In cisplatin-ineligible patients, immunotherapy in Programmed Death Ligand 1 (PD-L1)-positive patients or carboplatin in PD-L1–negative patients is recommended. For second-line treatment in metastatic disease, pembrolizumab is recommended. Postchemotherapy surgery may prolong survival in responders. Quality of life should be monitored in all phases of treatment and follow-up. The extended version of the guidelines is available at the EAU website: https://uroweb.org/guideline/bladder-cancer-muscle-invasive-and-metastatic/. This summary of the 2020 EAU MMIBC guideline provides updated information on the diagnosis and treatment of MMIBC for incorporation into clinical practice. The European Association of Urology Muscle-invasive and Metastatic Bladder Cancer (MMIBC) Panel has released an updated version of their guideline, which contains information on histology, staging, prognostic factors, and treatment of MMIBC. The recommendations are based on the current literature (until the end of 2019), with emphasis on high-level data from randomised clinical trials and meta-analyses and on the findings of an international consensus meeting. Surgical removal of the bladder and bladder preservation are discussed, as well as the use of chemotherapy and immunotherapy in localised and metastatic disease. Radical cystectomy with urinary diversion remains the mainstay of managing muscle-invasive bladder cancer (MIBC). The use of neoadjuvant chemotherapy (NAC) has improved overall survival rates, but selection of patients who will benefit most from NAC remains challenging. In case bladder-preserving strategies are considered, patient stratification according to their risk profile is imperative and management should be discussed in a multidisciplinary team. As yet, there are no validated prognostic molecular markers to guide the clinical management of MIBC. In a metastatic setting, cisplatin-based chemotherapy remains the first choice in fit patients. In unfit patients, based on interim results from two on-going clinical trials, first-line treatment with pembrolizumab or atezolizumab for urothelial cancer is restricted to Programmed Death Ligand 1-positive patients only.